An efficient looped multiple-stage thermoacoustically-driven cryocooler for liquefaction and recondensation of natural gas. (15th April 2016) - Xu, Jingyuan; Zhang, Limin; Hu, Jianying; Wu, Zhanghua; Bi, Tianjiao; Dai, Wei; Luo, Ercang
Abstract: With increasing demand for liquefied natural gas, high-efficiency and compact facilities are vital for dealing with natural gas liquefaction or boiled-gas recondensation. This study introduces a looped multiple-stage thermoacoustically-driven cryocooler system that operates in the temperature range of natural gas liquefaction and which has good prospects for meeting such demand. Because of the looped configuration, the system has the potential to achieve efficient traveling-wave thermoacoustic conversion and acoustic power transmission. The basic operating principles are described. A thorough numerical simulation is performed on the influence of the flow-area ratio of the regenerator to that of the resonance tube, which is found to be critical to system performance. To better understand the mechanism, acoustic impedances of the heat engine regenerator and the exergy losses are presented. The dependence of the load impedance on the flow-area ratio is also discussed. An experimental setup was built to verify the numerical simulation. The experimental results show good consistency with those of the simulation. The experimental system achieved a maximum total cooling capacity of 880 W and exergy efficiency of 7.8% at 110 K, corresponding to 65% liquefied natural gas production-efficiency for incoming gas at 300 K or about 74% recondensation efficiency for boiled gas. Highlights: An efficient three-stage thermoacoustically-driven cryocooler system is developed. Exergy efficiency of 7.8% and 880 W cooling capacity at 110 K was achieved. Regenerator–resonator flow-area ratio and cooling load impedance are key parameters. Operation is explained by analysis of acoustic impedance and exergy loss.